Penurunan logam Hg dalam air menggunakan sistem sub-surface flow constructed wetland: studi efektivitas - Rikhanatul Firdausy Puspitasari; Agus Prasetya; Edia Rahayuningsih (Jurnal Rekayasa Proses, 2019)
High amount of Mercury contamination is commonly found in traditional gold mining areas. This problem might occur due to the use of amalgamation process in traditional gold extraction process by dissolving the gold-bearing rocks with mercury (Hg). The utilization of mercury in gold mining activity has contaminated the water with Hg which might lead to serious health problems. This research was carried out by discharging the Hg-contaminated wastewater to enter a system called the Sub-Surface Flow Constructed Wetland (SSF-SW). The system employed a mixture of soil and the fibers of water hyacinth as the media on which Echinodorus palaefolius L. was planted. The wastewater containing HgCl2 at 8.59 mg/L was flown. The flow rate and pH were set to 6.3 L/hour and 6-7 pH at room temperature. Samples were collected at 0; 3.5; 7; 10.5 hours every day. The SSF-CW system was continually run for 10.5 hours and 13.5hour batch. The result of this research showed that the efficiency of Hg removal reached 92.79%. The results showed that the SSF-CW offers a stable system to reduce the mercury levels as shown in the growth of the plant and the total Hg removal efficiency. Plants with Hg exposure have distinct patterns of chlorosis. Some leaves turning yellow and die, others start with new growth. In addition, the growth of Echinodorus palaefolius L. was also influenced by the amount of nutrients in the soil.